The effects of Garcinia cambogia (hydroxycitric acid) on serum leptin concentrations: A systematic review and meta-analysis of randomized controlled trials - Mohammad Reza Amini; Marieh Salavatizadeh; Shervin Kazeminejad; Fozhan Javadi; Mahdi Hajiaqaei; Gholamreza Askari; Azita Hekmatdoost (Elsevier, 2024)
Objective: The observed impacts of Garcinia cambogia (GC) on serum leptin indicate inconsistency. We performed a systematic review and meta-analysis on randomized controlled trials (RCTs) to evaluate the effectiveness of GC on leptin levels. Methods: A thorough literature search was carried out using different online databases, including Scopus, Web of Science, PubMed, and Google Scholar, until May 25, 2024. Using random effects, weighted mean differences (WMDs) and corresponding 95 % confidence intervals (CIs) were computed. Standard procedures were followed to account for publication bias, study quality, and statistical heterogeneity. Results: In this meta-analysis, a total of eight eligible trials with 330 participants were ultimately included. Quality assessment showed that half of the included trials were considered to have fair quality, while the other half were deemed to have poor quality. Our analysis, with no indication of publication bias, showed a significantly decreased effect of GC on leptin compared with the placebo (WMD: −5.01 ng/ml; 95 % CI: −9.22 to −0.80, p = 0.02). However, significant heterogeneity was detected between studies (I2 =93.5 %, p < 0.001). The Hartung-Knapp adjustment did not affect our results. Subgroup analysis revealed that GC consumption represents the most effects in trials with sample size ≥ 50 (WMD: −3.63 ng/ml; 95 % CI [−5.51, −1.76], p < 0.001), and mean age of participants ≥ 30 years (WMD: −7.43 ng/ml; 95 % CI [−9.31, −5.56], p < 0.001). Conclusions: The findings of the present study showed that leptin levels might decline following GC administration. Registration number: CRD42023486370